The study of epidemiological, clinical, histopathological and dermoscopic features of lichen planus - Horatti, Laxmi B.; Rayapati, Abhiram; N. R., Dilip Kumar; A. R., Shashikiran (International Journal of Research in Dermatology, 2021)
Background: Lichen planus (LP) is a common papulosquamous condition seen by the dermatologists. It can involve the skin, mucous mebranes, hair and nails. There are many subtypes of LP with various clinical, histopathological and dermoscopic features. In this study we intended to study the epidemiological, clinical, histopathological and dermoscopic features of LP. Methods: A total of 73 patients of LP, above the age of 18 years who qualified the inclusion and exclusion criteria were included in the study. A proforma of epidemiological details was noted, clinical and dermoscopic examination of the lesions were done. The punch biopsy specimens of cutaneous lesions were subjected to histopathological examination and the findings noted. Results: Out of the 73 patients included in the study, 44 were males and 29 females with a ratio of 1.51:1. Classic LP was the commonest type of LP. Wickham’s striae (WS) was the most typical and commonest dermoscopic feature of cutaneous LP except lichen planus pigmentosus. Hyperkeratosis, hypergranulosis, acanthosis, band shaped lymphocytic infiltrate, melanophages, basal cell degeneration and saw tooth shaped rete ridges were the significant histopathological features. Conclusions: LP is more common in young adults and shows a male preponderance. WS is the most important diagnostic feature seen on dermoscopy of all the cutaneous types of LP excluding LPP. Interface dermatitis with a band of lymphocytic infiltrates and dermal melanophages is a notable feature of histopathology of LP.